Advanced silk materials for musculoskeletal tissue regeneration - Nie, Kexin; Zhou, Sicheng; Li, Hu; Tian, Jingyi; Shen, Weiliang; Huang, Wenwen (Frontiers in Bioengineering and Biotechnology, 2023)
Musculoskeletal diseases are the leading causes of chronic pain and physical disability, affecting millions of individuals worldwide. Over the past two decades, significant progress has been made in the field of bone and cartilage tissue engineering to combat the limitations of conventional treatments. Among various materials used in musculoskeletal tissue regeneration, silk biomaterials exhibit unique mechanical robustness, versatility, favorable biocompatibility, and tunable biodegradation rate. As silk is an easy-to-process biopolymer, silks have been reformed into various materials formats using advanced bio-fabrication technology for the design of cell niches. Silk proteins also offer active sites for chemical modifications to facilitate musculoskeletal system regeneration. With the emergence of genetic engineering techniques, silk proteins have been further optimized from the molecular level with other functional motifs to introduce new advantageous biological properties. In this review, we highlight the frontiers in engineering natural and recombinant silk biomaterials, as well as recent progress in the applications of these new silks in the field of bone and cartilage regeneration. The future potentials and challenges of silk biomaterials in musculoskeletal tissue engineering are also discussed. This review brings together perspectives from different fields and provides insight into improved musculoskeletal engineering.